Estudo experimental do efeito de grupo de estacas escavadas em perfil de solo granular - Bonan, Victor Hugo Fernandes (2017)
A foundations project must meet at least the following basic requirements: a) acceptable deformations under the working conditions; B) adequate security to the foundation soil collapse; and (c) adequate safety for the structural elements collapse. When using piles to design a project, depending on the distance between them, the behavior of one interferes with the other. This occurs both in terms of load capacity and settlement. Research on the group effect in typical soils of Fortaleza is scarce, justifying and motivating research on the subject. The aim of this research is to evaluate the group effect of excavated piles on granular soil profiles, typical of those that occur in the subground of the city of Fortaleza. For this, a bibliographic review was initially carried out on the subject. Subsequently, 26 piles were performed on a site, inside the campus of UFC (Experimental Field of Geotechnics and Foundations of UFC), isolated and in groups of 2 and 4 piles, varying the spacing between them. The subsoil was characterized from the collection of geotechnical test results that were previously performed at the site. In addition, a Standard Penetration Test (SPT) was performed, which had its resistance indexes (NSPT) corrected in function of efficiency estimates. Subsequently, Static Load Tests (SLT) on piles were carried out. The results of the static load tests on the executed piles, isolated and in groups, were compared with estimations made from methods established in the literature. It was observed that the executed piles work only by lateral friction. It was verified Group effect at all spacings investigated.